Da-Bu-Yin-Wan and Qian-Zheng-San Ameliorate Mitochondrial Dynamics in the Parkinson’s Disease Cell Model Induced by MPP+ - Gai, Cong; Feng, Wan-Di; Qiang, Tian-Yao; Ma, Hao-Jie; Chai, Yuan; Zhang, Shu-Jing; Guo, Zhen-Yu; Hu, Jing-Hong; Sun, Hong-Mei (Frontiers in Pharmacology, 2019)
To investigate the effect of Da-Bu-Yin-Wan and Qian-Zheng-San (DBYW & QZS) on mitochondrial mass in Parkinson's disease (PD) cell model induced by 1-Methyl-4-phenylpyridinium Ion (MPP+). The SH-SY5Y cell was selected and treated with MPP+. The PD model was intervened with DBYW & QZS. CCK-8 method was used to detect the survival rate of cells in each group. Mitochondria was labeled by mitoTracker® Red CMXRos (MTR) probe and observed by laser scanning confocal microscope, and ImageJ software was used to process images and measure mitochondrial form factors; TMRM was used to detect mitochondrial membrane potential (ΔΨm); Luciferase method was used to detect cellular ATP levels; Western-Blot technique was applied to detect the expression levels of Parkin protein, and the expression levels of Mfn1, Mfn2, OPA1, Drp1 and Fis1. After MPP+ modeling, the cell survival rate, form factor (F-factor) and mitochondrial activity were decreased significantly. ΔΨm and ATP levels were decreased significantly. The expression levels of Parkin protein, Mfn1, Mfn2 and OPA1 were decreased significantly. However, MPP+ treatment would dramatically increase the expression of Drp1 and Fis1. Compared with the model group, after treatment with DBYW & QZS, the cell survival rate, mitochondrial form factors and activity, ΔΨm were increased significantly; while the increase of ATP levels was not significantly. Additionally, DBYW & QZS significantly increased expression of Parkin protein and Mfn1, Mfn2 and OPA1 and a trend towards reduced expression of Drp1 and Fis1. DBYW & QZS has a certain protective effect on the injury of PD cells model induced by MPP+. The mechanism is associated with regulation the homeostasis between mitochondrial fission and fusion.